Kesukaran Item Kosa Kata Kerja Al-Quran Dalam Ujian Kosa Kata Al-Quran (QVT) Berdasarkan Model Pengukuran Rasch: Difficulty of Al-Quran Verb Vocabulary Items in the Qur'an Vocabulary Test (QVT) Based on the Rasch Measurement Model - Norudin, Nadzirah; Abu Bakar, Kaseh; Zainal, Hakim; Kamarudin, Mohamad Azwan (Al-Basirah Journal, 2021)
This study aims to measure the level of difficulty of a number of vocabulary instrument items in the Quranic Vocabulary Test (QVT) as well as the level of respondents' mastery of the items. The respondents of the study consisted of 69 undergraduate students of Universiti Kebangsaan Malaysia, who are Muslims and have various backgrounds in their studies. This study is quantitative by using the Rasch Measurement Model as a tool to achieve the two objectives outlined. The results of the study found that the frequency of an item does influence the determination of the level of difficulty of the item and the respondents' mastery of it.